EDI for consumers, personal assistants and ambient intelligence: the right to be forgotten - Andrade, Francisco Carneiro Pacheco (2018)
Electronic Data Interchange has been around for more than 20 years but it is now on the verge of transition to the new environments of the Networked Society, along with Personal Assistants, the Internet of Things and Ambient Intelligence, all aimed at relations with consumers. The commercial relationships will have to be rethought and reshaped, and Privacy and Data Protection will be at stake. It is the moment to look at the right to be forgotten froma perspective of the B2C commercial relationship.